30.5k views
1 vote
8. Solve the system of linear equations. y = 6x + 7 3x - y = 2 A. (-3,-11) B. (-2,-8) C. (-1,1) D. no solution

User Kinna T
by
5.2k points

1 Answer

2 votes

We have two equations and two unknowns.

y = 6x+7

3x - y = 2

Since the first equation is solved for y, we can substitute the right hand side in for y on the second equation

3x - y =2

3x - (6x+7) = 2

Distribute the minus sign outside of the parentheses

3x -6x -7 =2

Combine like terms

-3x -7 =2

Add 7 to each side

-3x-7+7 = 2+7

-3x = 9

Divide each side by -3

-3x/3 = 9/-3

x =-3

Now we need to find y

Substitute into the first equation

y = 6x+7

y = 6(-3) +7

=-18+7

=-11

The solution is (-3, -11)

User Susmit Agrawal
by
5.3k points